Preventive Maintenance Case Study : Car Seat Manufacturing Company - อินทรีย์มีศักดิ์ บัณฑิต; จาตุนิตานนท์ ภูมิ; กังหัน วรวุฒิ (SAU JOURNAL OF SCIENCE & TECHNOLOGY, 2021)
The failure of machinery in the car seat production process is a main problem of industrial plants. Therefore, the researcher proposed the preventive maintenance method for improving the efficiency of the operation of machine. From the obtained data of the machine maintenance period, resulting in the production line being more efficient, and machine availability increased from 87.86% per month to 96.98% per month. Mean Time to Repair (MTTR) decreased by 121 hours per month to 57 hours per month. Mean Time Between Failures (MTBF) increased from 878.6 hours per month to 1,920 hours per month. The average value of losses decreased from 50,670 baht per month to 34,050 baht per month, when applying the preventive maintenance method in the car seat production line.